Asian Soybean Rust - Wayne M. Jurick II; Dario F. Narvaez; Carrie L. Harmon; James J. Marois; David L. Wright; Philip F. Harmon (EDIS)
PP-235, a 4-page illustrated fact sheet by Wayne M. Jurick II, Dario F. Narvaez, Carrie L. Harmon, James J. Marois, David L. Wright, and Philip F. Harmon, describes this fungal plant disease new to the US since 2004, its symptoms, causal organism, disease cycle and epidemiology, diagnosis, and management. Includes links to web-based resources and references. Published by the UF Department of Plant Pathology, July 2007.